Best practices in evaluating work integration social enterprises for persons with intellectual disabilities: A scoping review. Issue 4 (1st September 2022) - Lysaght, Rosemary; Ghaderi, Golnaz; Milley, Peter; Labelle, Patrick R.
Abstract: Social enterprise is emerging as a promising means of creating flexible employment transitions for people with intellectual disabilities. It has been adopted as an option largely in response to the extended periods of work adjustment and ongoing supportive work environments typical for this population, as well as challenges in identifying suitable and satisfying job matches in the conventional labour market. Creation of meaningful and sustainable employment in social enterprises resides at the intersection of social programming and business management, such that developers must attend to employee needs from a human resource and skills development perspective, while equally attending to sound business management practices. This scoping review aimed to identify best practices for evaluating emerging work integration social enterprises using established program evaluation methods as a means of guiding and monitoring practice. Sixteen studies met study selection criteria, and while not directly addressing the issue of evaluation quality, revealed a number of principles and practices for consideration by evaluators. Implications for evaluation practice are highlighted.